CRAT missense variants cause abnormal carnitine acetyltransferase function in an early‐onset case of Leigh syndrome. Issue 1 (23rd September 2019) - Laera, Luna; Punzi, Giuseppe; Porcelli, Vito; Gambacorta, Nicola; Trisolini, Lucia; Pierri, Ciro L.; De Grassi, Anna
Abstract: Leigh syndrome, or subacute necrotizing encephalomyelopathy, is one of the most severe pediatric disorders of the mitochondrial energy metabolism. By performing whole‐exome sequencing in a girl affected by Leigh syndrome and her parents, we identified two heterozygous missense variants (p.Tyr110Cys and p.Val569Met) in the carnitine acetyltransferase ( CRAT ) gene, encoding an enzyme involved in the control of mitochondrial short‐chain acyl‐CoA concentrations. Biochemical assays revealed carnitine acetyltransferase deficiency in the proband‐derived fibroblasts. Functional analyses of recombinant‐purified CRAT proteins demonstrated that both missense variants, located in the acyl‐group binding site of the enzyme, severely impair its catalytic function toward acetyl‐CoA, and the p.Val569Met variant also toward propionyl‐CoA and octanoyl‐CoA. Although a single recessive variant in CRAT has been recently associated with neurodegeneration with brain iron accumulation (NBIA), this study reports the first kinetic analysis of naturally occurring CRAT variants and demonstrates the genetic basis of carnitine acetyltransferase deficiency in a case of mitochondrial encephalopathy.